Comparative investigation of worm positions for worm gearbox performance under no-load condition / Hardik G Chothani and Kalpesh D Maniya - Chothani, Hardik G; Maniya, Kalpesh D (Universiti Teknologi MARA, 2021)
The Worm Gear drive is a gear arrangement where the worm shaft meshes with a worm wheel (gear). The worm shaft plays an important role in reduction ratio & efficiency. This worm shaft can be used at the top and the bottom in the gearbox. This technical research paper provides a comprehensive comparative evaluation of Input torque analysis & heating rate of lubricant inside the gearbox for two positions of the worm shaft in the worm gearbox under no-load condition. Worm shaft at the top and worm shaft at the bottom were assessed at variable speed (1000-1400 rpm), the different splashed volume of lubricant (1.5-2.7 liter), and variable temperature of lubricant (30-50 ºC). Input torque was measured with the help of a direct torque measurement technique. Similarly, the heating rate of the lubricant was also measured with a temperature sensor for both orientations of the worm shaft. Full factorial experiments were performed on a specially designed and fabricated worm gear test rig. The experiments showed that the input torque requirement for the worm at the bottom position is 20 -25% higher than the worm at the top position at an average speed. The heating rate remains almost the same for both orientations. This study aimed to find the suitable orientation of the worm shaft which reduces the power losses and increases efficiency.